2022
DOI: 10.5223/pghn.2022.25.4.283
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Eosinophilic Esophagitis in Patients with Cystic Fibrosis: A Population-Based 5-Year Study

Abstract: Purpose The prevalence of eosinophilic esophagitis (EoE) has been on the rise since it was first described in the 1990s. Several diseases and exogenous factors have been associated with EoE. Our aim was to investigate the epidemiology of EoE in cystic fibrosis (CF) patients. Methods We identified individuals with CF from September 2014 to September 2019 within a database (IBM Explorys Solutions, Inc.). The prevalence of EoE in patients with CF was compared to the genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…PwCF may experience an increased incidence of other esophageal diseases. Eosinophilic esophagitis, a chronic inflammatory disease of the esophagus often associated with food allergies, appears to be increased in pwCF compared with the general population 22 . The cause is not clear but may be due to a genetic effect or immune dysfunction.…”
Section: Pathophysiology Of the Cf Gi Tractmentioning
confidence: 99%
See 3 more Smart Citations
“…PwCF may experience an increased incidence of other esophageal diseases. Eosinophilic esophagitis, a chronic inflammatory disease of the esophagus often associated with food allergies, appears to be increased in pwCF compared with the general population 22 . The cause is not clear but may be due to a genetic effect or immune dysfunction.…”
Section: Pathophysiology Of the Cf Gi Tractmentioning
confidence: 99%
“…Eosinophilic esophagitis, a chronic inflammatory disease of the esophagus often associated with food allergies, appears to be increased in pwCF compared with the general population. 22 The cause is not clear but may be due to a genetic effect or immune dysfunction. Eosinophilic esophagitis should be considered in pwCF who have associated feeding problems, chronic emesis, dysphagia/odynophagia, GERD-like symptoms not responsive to acid suppression therapy, and a history of food impaction.…”
Section: Pathophysiology Of the Cf Gi Tract Esophagusmentioning
confidence: 99%
See 2 more Smart Citations
“…Small case series of pediatric patients with CF have described associated CD, eosinophilic esophagitis (EoE), and inflammatory bowel disease [11][12][13][14][15][16]. Furthermore, studies including both adults and children with CF have demonstrated a potential increased incidence of CD and EoE [5,17].…”
Section: Introductionmentioning
confidence: 99%